Rentabilidad de la empresa Best-Quality-Fruit S.A. de la ciudad de Guayaquil de los periodos 2021-2022. - Arana Zamora, Glenda Zalle (2024)
The analysis of the profitability of Best-Quality-Fruit S.A., located in Guayaquil, during the periods 2021 and 2022, reveals a significant decrease in its total assets, especially in current assets and cash equivalents, suggesting issues in cash management and the recovery of accounts receivable. The research is justified by the need to provide a solid foundation for strategic and financial decision-making in a competitive and volatile market. The main objective of the study was to evaluate the company's profitability through the analysis of financial statements and the application of financial profitability indicators. The methodology used included a mixed approach, combining qualitative and quantitative analysis of the financial statements. The results indicate a decrease in the company's profitability and operational efficiency, with a notable decline in the net profit margin and the return on assets and equity. The conclusions highlight the need for more efficient management of operating costs and better utilization of resources to reverse the negative trend and improve the profitability of Best-Quality-Fruit S.A.